Pelaksanaan Program Usaha Ekonomi Desa Simpan Pinjam (UED-SP) Dalam Pemberdayaan Masyarakat Di Desa Serai Wangi Kecamatan Pinggir Kabupaten Bengkalis - Tarmi "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Observational background is Program UED-SP as effort of government to tackling society hole in the wall at peberdayaan's area ala economy gets moving but UED-SP relief fund Receiver that more relative society has intermediate and intermediate economy onto compared with by society hole in the wall. Besides available many constraints in conection with UED-SP activity performing as looked as effective reducing performing programs this, it at proves by its happening paying installment arrears each month it and fund abuse by that UED- SP member.To the effect research which is to know member that gets to program UED SP Effort Partner with membered prospective verification process UED SP and UED SP'S member establishment and to know UED SP'S Program performing at Desa Serai Wangi Kecamatan Pinggir Kabupaten Bengkalis by sees success, failing, managing observation and sanction for performing to program UED SP. This research utilizes Structural Functional and Motivation in performing Programs UED SP. Method that is utilized is kualitatif that gets character descriptiving to get information about UED-SP program performing. Research does visceral interview with managing UED-SP and society that becomes UED- SP member.Of finding result at field can be known that UED-SP Effort Partner at Silvan serai Fragrant in its imprecise performing objective and a lot of delinquent. It was caused by karna be not been carried on it process verifies with maximal by verification team and marks sense fund and behaviour abuse that inauspicious by membered UED-SP besides frail it organizer observation and less explicit it sanction for performing to program UED-SP.Key word: Performing Programs UED SP, Empowerment and Society welfare